The Influence of product quality on halal cosmetics purchase decisions: Examining the mediating effects of Islamic branding and halal awareness - Maksum; Ifunanya Nkechi Ohamobi; Muktirrahman; M. Fayyad Zainal Abidin (Alkasb: Journal of Islamic Economics, 2025)
This study examines how product quality influences halal cosmetics purchase decisions among religiously educated Muslim consumers and investigates the moderating roles of Islamic branding and halal awareness—a theoretical relationship underexplored in faith-based marketing literature. Using PLS-SEM analysis, data from 95 female Islamic boarding school students (santriwati) in East Java, Indonesia were analyzed through structured questionnaires measuring product quality, Islamic branding, halal awareness, and purchase decisions. Product quality significantly influences purchase decisions (β=0.446, p<0.001). Islamic branding functions as a significant mediator (β=0.402, p=0.001), amplifying quality's effect. Unexpectedly, halal awareness shows direct effects (β=0.374, p=0.009) but no mediation, suggesting it operates as an independent driver rather than contextual enhancer. The model explains 66.0% of variance. This study challenges conventional assumptions by demonstrating that halal awareness operates independently rather than mediating quality evaluations, contributing novel insights to Islamic marketing theory and Muslim consumer behavior. Manufacturers should prioritize authentic quality while deploying Islamic branding strategically. Marketing to educated Muslim consumers requires demonstrable integration of functional excellence with sharia compliance.